Car Sharing in Marketing - Alexander Joseph Ibnu Wibowo; Ujang Sumarwan; Budi Suharjo; Megawati Simanjuntak (Jurnal Manajemen Indonesia, 2022)
The objective of this article is to explore several studies on Car Sharing (CS) in the marketing discipline. A total of 1,251 articles was collected from several journals in the Q1 Schimago category. Of these number 165 articles were chosen for research goals. A detailed investigation reduced this amount to 50 articles. The content analysis technique is applied by examining some key aspects, such as theme, authorship, research type, scope, and research design. The results of this study show that top-class journals have not published many articles about CS in the marketing discipline, but this does show an upward trend. Most articles are empirical papers. In general, the findings show a shift in the focus of CS studies in the marketing discipline over time. Keywords—Online transportation; Sharing economy; Car sharing; Marketing; Content analysis